<h3>
Answer: Reflect over the y axis</h3>
=====================================================
Explanation:
We have these two given functions
The change is that the x has been replaced with -x
We can say
f(x) = x+7
f(-x) = -x+7 ... replace each x with -x
g(x) = f(-x)
g(x) = -x+7
When we replace x with -x, we're flipping the x inputs from positive to negative, and vice versa. This visually will reflect the line over the vertical y axis. A point like (1,8) on f(x) reflects over to (-1,8) on g(x).
As another example, the point (-5,2) on f(x) reflects over the y axis to arrive at (5,2) on the g(x) function.